2013
DOI: 10.1152/ajpendo.00409.2012
|View full text |Cite
|
Sign up to set email alerts
|

The mTORC1 signaling repressors REDD1/2 are rapidly induced and activation of p70S6K1 by leucine is defective in skeletal muscle of an immobilized rat hindlimb

Abstract: Kelleher AR, Kimball SR, Dennis MD, Schilder RJ, Jefferson LS. The mTORC1 signaling repressors REDD1/2 are rapidly induced and activation of p70S6K1 by leucine is defective in skeletal muscle of an immobilized rat hindlimb. Am J Physiol Endocrinol Metab 304: E229 -E236, 2013. First published November 27, 2012; doi:10.1152/ajpendo.00409.2012.-Limb immobilization, limb suspension, and bed rest cause substantial loss of skeletal muscle mass, a phenomenon termed disuse atrophy. To acquire new knowledge that will a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 54 publications
9
118
1
Order By: Relevance
“…To determine the rate of cardiac global protein synthesis, puromycin (Sigma; 40 mol⅐kg ÏȘ1 of body weight) was intravenously injected to isofluorane-anesthetized animals (9). The heart was harvested 10 min after the injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the rate of cardiac global protein synthesis, puromycin (Sigma; 40 mol⅐kg ÏȘ1 of body weight) was intravenously injected to isofluorane-anesthetized animals (9). The heart was harvested 10 min after the injection.…”
Section: Methodsmentioning
confidence: 99%
“…5C), indicating activation of the mTOR pathway in these hearts. To investigate whether this alteration in mTOR signaling could result in changes in the protein synthesis process, we measured the rate of protein synthesis in vivo using the puromycin incorporation method (9). Despite the activation of mTOR pathway in Mlip ÏȘ/ÏȘ hearts, the steady state of protein synthesis was similar in Mlip ÏȘ/ÏȘ and Mlip Ï©/Ï© hearts (Fig.…”
Section: Mlip Regulates the Cardiac Activity Of Akt/mtor Signalingmentioning
confidence: 99%
“…Indeed, numerous studies demonstrated that a reduction in muscle protein fractional synthesis rate (FSR) occurs in the first days of immobilization [53,75,76]. This rapid reduction of protein synthesis persists for several weeks since a decrease of muscle FSR has been also reported in human skeletal muscle after 14 and 28 days of bed rest [77,78].…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 99%
“…Interestingly, skeletal muscle exhibits alteration in PI3K/Akt/mTORC1 axis during immobilization [75,76,[80][81][82]. This phenomenon, called anabolic resistance, emphasizes the reduced response to anabolic stimuli [80,82].…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 99%
“…[17][18][19] Atrophy can be induced experimentally through hindlimb suspension, hindlimb immobilization, chemical denervation (botulinum toxin), and surgical denervation (severing the nerve). [20][21][22][23][24] All these methods share the common trait of reducing or completely inhibiting neural input to the muscle, which induces atrophy. Denervation of adult muscles can revert the expression of specific genes to an embryonic expression profile.…”
mentioning
confidence: 99%